Antimicrobial activity of Backhousia citriodora (lemon myrtle) methanolic extracts - IE, Cock (Pharmacognosy Communications)
Introduction: Backhousia citriodora is a native Australian plant with uses as a bush food component as well as in toiletries and cosmetics. Essential oils produced from leaves of this plant have reputed antiseptic properties. Despite this, solvent extractions of Backhousia citriodora leaves have not been rigorously examined for antiseptic properties. Methods: The antimicrobial activity of methanolic leaf extracts of Backhousia citriodora was investigated by disc diffusion and growth time course assays against a panel of bacteria and fungi. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: B. citriodora leaf methanolic extract proved to be a versatile antibacterial agent inhibiting the growth of 12 of the 14 bacteria tested (86%). Only C. fruendii and S. aureus growth were unaffected by B. citriodora extract. Gram-positive and Gram-negative bacteria were both affected by B. citriodora extract although Gram-negative bacteria appeared more susceptible. The extract also displayed antifungal activity against a nystatin resistant strain of Aspergillus niger but did not affect Candida albicans or Saccharomyces cerevisiae growth. The antibacterial activity of B. citriodora extract was further investigated by growth time course assays which showed significant growth inhibition in cultures of Bacillus cereus, Bacillus subtilis, Aeromonas hydrophilia and Pseudomonas fluorescens within 1 h. The extract displayed low toxicity in the Artemia franciscana nauplii bioassay. Conclusions: The low toxicity of the methanolic extract and its inhibitory bioactivity against a panel of bacteria validate Australian Aboriginal usage of B. citriodora as an antiseptic agent and confirms its medicinal potential.
Keywords: Backhousia citriodora; lemon myrtle; Australian plants; antibacterial activity; medicinal plants; methanol extracts